2015
DOI: 10.1111/asap.12074
|View full text |Cite
|
Sign up to set email alerts
|

Using Moral Foundations to Predict Voting Behavior: Regression Models from the 2012 U.S. Presidential Election

Abstract: The current research examined the ability of moral foundations to predict candidate choice in the 2012 U.S. Presidential Election across three studies. Results indicated that endorsement of moral foundations predicted voting outcomes beyond that predicted by important demographic variables that are traditionally included in election forecasts and research. When moral foundations were collapsed into two variables (individualizing and binding foundations), increased endorsement of the individualizing foundations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
62
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(75 citation statements)
references
References 40 publications
6
62
0
1
Order By: Relevance
“…; Schein and Gray ). The overwhelming majority of MFT applications assume that Moral Foundations cause political beliefs, or at a minimum that patterns of moral intuitions captured by Moral Foundations reliably predict political beliefs (e.g., Franks and Scherr ; Haidt ; Inbar, Pizarro, and Bloom , ; Kertzer et al. ; Koleva et al.…”
Section: The Causal Path Between Morality and Ideologymentioning
confidence: 99%
See 1 more Smart Citation
“…; Schein and Gray ). The overwhelming majority of MFT applications assume that Moral Foundations cause political beliefs, or at a minimum that patterns of moral intuitions captured by Moral Foundations reliably predict political beliefs (e.g., Franks and Scherr ; Haidt ; Inbar, Pizarro, and Bloom , ; Kertzer et al. ; Koleva et al.…”
Section: The Causal Path Between Morality and Ideologymentioning
confidence: 99%
“…As such, they hold obvious importance, yet the extant research provides no clear answers. Given the growing scholarship using MFT as an explanation of political values (e.g., Clifford ; Clifford and Jerit ; Franks and Scherr ; Kertzer et al. ; Koleva et al.…”
mentioning
confidence: 99%
“…Past research has shown that liberals and conservatives rely on these moral foundations to different degrees; compared to liberals, conservatives tend to rely more on sanctity (and loyalty and authority), and less on fairness (and care; Graham et al., ). Individual differences in concerns about sanctity predict attitudes on an array of issues, such as abortion, euthanasia, and pornography (Koleva, Graham, Iyer, Ditto, & Haidt, ) and candidate endorsement in the 2012 U.S. Presidential election (Franks & Scherr, ). Moral foundations also explain individual differences in political involvement.…”
Section: Introductionmentioning
confidence: 99%
“…Both between and within cultures, MFT has also been used to explore differences in voting behaviour and attitudes between people on the political left and right. In a practical example, responses to an MFT questionnaire had strong predictive validity for forecasting how people voted in the 2012 American election (Franks & Scherr, 2015).…”
mentioning
confidence: 99%